Exosomes and miRNA-Loaded Biomimetic Nanovehicles, a Focus on Their Potentials Preventing Type-2 Diabetes Linked to Metabolic Syndrome - Beuzelin, Diane; Kaeffer, Bertrand (Frontiers in Immunology, 2018)
Exosomes are small membrane vesicles of 30–150 nm, members of the extracellular vesicle family and secreted by various cell types. Different studies describe specific microRNA (miRNA) with altered expression in serum and/or plasma of patients suffering from diabetes or metabolic syndrome. Diabetic cardiomyocyte-derived exosomes loaded with miRNAs like miR-320-3p (or 320a) have been shown regulating angiogenesis on endothelial cell cultures. Insufficient myocardial angiogenesis is the major manifestation of diabetes-caused ischemic cardiovascular disease. Studies on transfer of functional microRNAs between mouse dendritic cells via exosomes have shown that some miRNAs (miR-320-3p, 29b-3p, 7a-5p) are distributed in immature and mature exosomes. Among these miRNAs, miR-320-3p is better known in epigenetics for silencing polr3d gene by binding to its promoter in Human Embryonic Kidney-293 cells. Moreover, quantitative and stoichiometric analysis of the microRNA content of exosomes highlights the lack of reliable natural source of such particles loaded with miRNA opening the need for tailoring exosomes or nanoparticles delivering efficiently miRNA intimately linked to immunity, metabolism and epigenetics in target cells. However, loading of extracellular mature miRNA into recipient cells comes with a cost by at least impeding dynamic localization of miRNAs in nucleoli or inefficient miRNA delivery due to rapid recycling by exonucleases. All these works are calling for the design of new biomimetic vehicles and in vivo assessment of miRNA functionality when delivered by natural or biomimetic nanoparticles in order to control metabolic diseases from infancy to adulthood.